Composition of small and large firms' business networks in transition economies - Ferreira, Manuel Portugal (2011)
Recent research has theorized on the composition of firms' business networks but has not empirically examined business networks in transition economies may vary for different firms. In this study, using firm level data from twenty six transition economies collected by the World Bank and the EBRD in 1999-2000, we conduct a set of logistic regression models to investigate the composition of small and large firms' business networks. The results show that, in contrast to smaller firms, larger firms are more likely to have formal business relationships, and relationships with national and foreign financial institutions, government, and foreign firms. In addition, in a subgroup analysis of seven transition economies we show that the composition of the firms' business networks varies substantially across countries but that the government is still a dominant client. Furthermore, we found a large variation on firms' reliance on informal ties and the extent to which firms exchange with foreign firms.